A longitudinal study of physical fitness in elite junior tennis players - Kramer, T.; Huijgen, B. C. H.; Elferink-Gemser, M. T.; Visscher, C. (Pediatric Exercise Science, 2016)
Purpose: To analyze how physical fitness (PF) improves in elite junior tennis players related to age, maturity, and performance level. Methods: Elite junior tennis players (n = 113 boys, n = 83 girls) divided by performance level were monitored longitudinally from U14 to U16. Maturity, upper and lower-body power, speed, and agility were measured during subsequent competitive seasons. Improvement was analyzed per sex using multilevel analysis. Results: PF components for boys and girls improved over age (U14-U16) (ES .53-.97). In boys, the more mature boys outscored the less mature boys in upper and lower-body power from U14-U16. In girls, high-ranked girls outscored lower-ranked girls on lower-body power, speed, and agility (U14-U16) (p < .05). Conclusion: Boys and girls improved on all PF components during U14-U16. In boys, power was related to maturity. In girls, lower-body power, speed, and agility were related to tennis performance. This has important implications for talent development.